Kinetics and Thermodynamics of Bleaching Process in Aqueous Solution using Sodium Hypochlorite - Okeola, F. O.; Nwosu, F. O.; Abu, T. O.; Odebunmi, E. O.; Owolabi, O. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The kinetics of bleaching process of oxidation of typical dye with a bleaching agent - sodium hypochlorite in aqueous medium was studied. The kinetic runs were executed using spectrophotometer to changes in concentration under pseudo first order whereby concentration of NaOCl was in large excess compared with the concentration of dye. The factors affecting the reaction rate that were studied include the concentration of dye and oxidant, temperature, ionic strength and pH of the bleaching reaction medium and the presence of a variable valence metal ion The result shows that the rate of oxidation increases with increasing in temperature, ionic strength and pH. Increasing in substrate and oxidant concentrations also increase the rate of oxidation. Higher observed rate constant k1 was obtained in the presence of Fe(III)ion. The Arrhenius activation energy for the oxidation in the absence and presence of Fe(III)ion are 56.21 kJmol-1 and 51.21 kJmol-1 respectively. The result of thermodynamic parameters such as the lowering of activation energy (Ea) and the higher value of second rate constants k2 in the presence of Fe (III) ion provide further support for Fe (III) ion enhancement of rate of oxidation.